Willingness to pay and pricing for broadband across the rural/urban divide in Canada. (March 2022) - Worden, David; Hambly, Helen
Abstract: Efforts to close the rural/urban digital divide in Canada have reached new heights in the wake of the ongoing COVID-19 pandemic and "stay-at-home" policies. Yet the extent to which the rural/urban digital divide extends to pricing and demand for broadband services is not well understood. Using a dataset of more than 4700 residential survey responses from southern Ontario, Canada, we assess the disparity in pricing and willingness to pay for broadband across rural and urban households. Our results suggest that rural users face higher installation and monthly fees while receiving a significantly inferior quality of service than their urban counterparts. Demand among rural users for improved broadband access is also higher than for urban users. These results may strengthen the business case for expanding broadband services into rural areas and/or supporting justification for public subsidization. Our analysis also suggests higher economic net benefits from prioritizing majority access at current federal service objectives rather than investing in a small number of users to receive higher quality broadband. Highlights: Rural users pay significantly more for broadband than urban users. Average monthly prices hide true fees for service in rural areas. After controlling for connection type and household factors, rural users pay 46 and 14 percent higher installation and monthly fees, respectively. Rural users have a high but concave willingness to pay for better broadband. High rural demand is a critical factor in prioritizing broadband investment.